PENERAPAN PROGRAM IN HOUSE TRAINING DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU PENDIDIKAN ANAK USIA DINI - Nopika Rosa (Universitas Pendidikan Indonesia, 2016)
Implementation of In House Training Programs in IncreasingPedagogical Competence Teacher of Early Childhood Education. Thisresearch was conducted with reference to the Permendiknas 16 , 2007 which describes the Academic Competence and Qualification of Teachers of early childhood education , particularly in the pedagogical competence. Thepurpose of this research is to see the profile of pedagogical competence ofteachers in early childhood Bee School and Early Childhood Grow Education through the implementation of In House Training program. The author uses collaborative approach. Sources of data in this research consisted of teachers in early childhood Bee School and Early Childhood Grow Education. Collecting data in this research using written tests, observation and documentation. Data analysis was performed by collecting field data based on the test results, observation and documentation. Findings from the research include: pedagogical competencies of teachers that includes the aspects of teachers' understanding of the development and characteristics of children, learning theories and learning principles, planning and implementation of learning, and assessment processes and learning outcomes.Penerapan Program In House Training dalam MeningkatkanKompetensi Pedagogik Guru Pendidikan Anak Usia Dini. Penelitian inidilakukan dengan merujuk pada Permendiknas No.16 Tahun 2007 yangmenjelaskan tentang Kompetensi Akademik dan Kualifikasi Guru PAUD,khususnya dalam kompetensi pedagogik. Tujuan dari penelitian ini adalahuntuk melihat profil kompetensi pedagogik guru di PAUD Bee School danPAUD Grow Education melalui penerapan program In House Training.Penulis menggunakan pendekatan kolaboratif. Sumber data dalam penelitian ini terdiri dari guru di PAUD Bee School dan PAUD Grow Education. Pengumpulan data pada penelitian ini menggunakan tes tertulis, pedoman observasi dan studi dokumentasi. Analisis data dilakukan denganmengumpulkan data dilapangan yang berdasarkan pada hasil tes, observasi dan studi dokumentasi. Temuan hasil penelitian ini meliputi: Kompetensi pedagogik guru yang mencakup pada aspek pemahaman guru terhadap perkembangan dan karakteristik anak, teori-teori belajar dan prinsip-prinsip pembelajaran, perencanaan dan pelaksanaan pembelajaran, serta penilaian proses dan hasil belajar.